The Influence Of K-Pop Artists As Brand Ambassadors On Affecting Purchasing Decisions And Brand Loyalty (A Study of Skincare Products in Indonesia Consumers In Indonesia) - Pardede, Bonita; Aprianingsih, Atik (Integrasi Sains Media, 2023)
One of the current promotional strategies adopted by many brands in Indonesia is leveraging the K-Wave (Hallyu) phenomenon. A skincare manufacturer aims to capitalize on this opportunity by appointing the popular K-Pop girl group, Twice as their brand ambassador. The significant investment in this collaboration raises high expectations for skincare products, particularly regarding their chosen brand ambassadors' impact on purchasing decisions and brand loyalty. Hence, this research aims to examine the influence of various dimensions (visibility, credibility, attractiveness, and power) of K-Pop artist Twice on skincare product consumers' purchasing decisions and brand loyalty. Furthermore, the study aims to investigate the mediating role of customer satisfaction in the relationship between purchasing decisions and brand loyalty among cosmetics product consumers. This research employs a non-probability purposive sampling technique, with a sample size of 200 respondents aged between 15 and 34 years, encompassing all genders. The respondents must have prior experience using cosmetics products and be aware of Twice as one of the skincare brand ambassadors. The data analysis technique employed is the Structural Equation Modeling (SEM) Partial Least Squares (PLS) method. The findings indicate that the dimensions of